Status and Perspective of Hospital Information Systems in Japan - Haruki, Y.; Ogushi, Y.; Okada, Y.; Kimura, M.; Kumamoto, I; Sekita, Y. (Methods of Information in Medicine, 1999)
Questionnaire surveys were sent to hospital managers, designed to shape the policy for future hospital information systems in Japan. The answers show that many hospitals use dedicated management systems, especially for patient registration and accounting, and personnel, food control, pharmacy and financial departments. In many hospitals, order-entry systems for laboratory tests and prescriptions are well developed. Half of the hospitals have patient databases used for inquiries of basic patient information, history of outpatient care and hospital care. The most obvious benefit is the reduction of office work, due to effective hospital information system. Many hospital managers want to use the following sub systems in the future for automatic payment, waiting time display, patient records search, automatic prescription verification, drug side-effect monitoring, and graphical display of patient record data.
Keywords: Hospital Information System; Questionnaire Survey; Evaluation